2021
DOI: 10.4103/jhrs.jhrs_21_20
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric antiphospholipid syndrome: An approach from glycans of the immunoglobulin G

Abstract: This is a case report of women with pregnancy morbidity (PM), some of them associated with antiphospholipid syndrome (APS), in which the glycan patterns of immunoglobulin G (IgG) were investigated based on the theory of alteration of glycosylation in autoimmunity. We used lectin blot to determine changes in terminal glycosylation of polyclonal IgG from women with antiphospholipid (aPL) antibodies and PM plus vascular thrombosis (PM/VT) and seronegative-obstetric APS (SN-OAPS). In addition, we analyzed IgG from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Thrombotic and obstetric APS may correspond to different diseases and may also have different pathogenic mechanisms despite sharing the same aPL 48–50 . Accordingly, we show that nitrosative stress is present mainly in the SN‐OAPS group characterized by increased levels of nitrosative markers, whereas IgG from this group of patients enhanced nitrotyrosine associated with reduced activation of eNOS in HUVECs.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Thrombotic and obstetric APS may correspond to different diseases and may also have different pathogenic mechanisms despite sharing the same aPL 48–50 . Accordingly, we show that nitrosative stress is present mainly in the SN‐OAPS group characterized by increased levels of nitrosative markers, whereas IgG from this group of patients enhanced nitrotyrosine associated with reduced activation of eNOS in HUVECs.…”
Section: Discussionmentioning
confidence: 67%
“…Because it has been suggested that the pathophysiological mechanisms of vascular APS are different from those of obstetric APS, [48][49][50] in this study we characterize nitrosative stress markers in serum of different clinically relevant groups of APS patients. We also evaluated the potential harmful effects of the polyclonal IgG purified from the serum of women with APS on the expression of nitrotyrosine and activation (i.e., serine 1177 phosphorylation) of eNOS in endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…IgG from the patient group with clinical features of PM but non-criteria aPL (SN-OAPS) also did not induce any responses in the endothelial cells, thus revealing specific mechanisms triggered by the classical pathological aPL present in patients with PM/VT and VT. We previously showed several in vitro effects induced by aPL from women with PM/VT when compared with aPL from women with PM alone, suggesting that these aPL are distinct and could be triggering other pathways, which leads to different and/or more complex clinical manifestations (Alvarez et al, 2015(Alvarez et al, , 2017. These subtle differences among the mechanisms triggered by aPL subpopulations have been suggested from prior studies (Ripoll et al, 2018;Alvarez et al, 2021). We also highlight that our cellular model was FBS-free, and since we did not performed any recombinant β2GPI addition, it is possible that cellular responses observed here were induced by aCL rather than aB2GPI antibodies.…”
Section: Discussionmentioning
confidence: 78%